Quality of Life and Toxicity after SBRT for Organ-Confined Prostate Cancer, a 7-Year Study - Katz, Alan Jay; Kang, Josephine (Frontiers in Oncology, 2014)
Objectives: Stereotactic body radiation therapy (SBRT) yields excellent disease control for low- and intermediate-risk prostate cancer by delivering high doses of radiation in a small number of fractions. Our report presents a 7-year update on treatment toxicity and quality of life (QOL) from 515 patients treated with prostate SBRT. Methods: From 2006 to 2009, 515 patients with clinically localized, low-, intermediate-, and high-risk prostate cancer were treated with SBRT using Cyberknife technology. Treatment consisted of 35–36.25 Gy in 5 fractions. Seventy-two patients received hormone therapy. Toxicity was assessed at each follow-up visit using the expanded prostate cancer index composite (EPIC) questionnaire and the radiation therapy oncology group urinary and rectal toxicity scale. Results: Median follow-up was 72 months. The actuarial 7-year freedom from biochemical failure was 95.8, 89.3, and 68.5% for low-, intermediate-, and high-risk groups, respectively (p < 0.001). No patients experienced acute Grade 3 or 4 acute complications. Fewer than 5% of patients had any acute Grade 2 urinary or rectal toxicity. Late toxicity was low, with Grade 2 rectal and urinary toxicity of 4 and 9.1%, respectively, and Grade 3 urinary toxicity of 1.7%. Mean EPIC urinary and bowel QOL declined at 1 month post-treatment, returned to baseline by 2 years and remained stable thereafter. EPIC sexual QOL declined by 23% at 6–12 months and remained stable afterwards. Of patients potent at baseline evaluation, 67% remained potent at last follow-up. Conclusion: This study suggests that SBRT, when administered to doses of 35–36.25 Gy, is efficacious and safe. With long-term follow-up in our large patient cohort, we continue to find low rates of late toxicity and excellent rates of biochemical control.